KENYAMANAN SIRKULASI ASRAMA MAHASISWA UNIVERSITAS NEGERI LAMPUNG (UNILA) BERDASARKAN PERSEPSI PENGHUNI - Munawaroh, Ai Siti; Jajuli, Ahmad; Kustiani, Kustiani (Jurnal Arsitektur ZONASI, 2020)
The function of a building can be achieved by fulfilling the comfort of its circulation. Previous studies have shown that circulation in the UNILA Student Dormitory circulation has fulfilled the comfort criterias even though in the bedroom there is still a crossing circulation.The purpose of this study is to find out the occupants' perceptions of circulation comfort in the UNILA Student Dormitory.This study uses a qualitative methods. While the data obtained through questionnaires were distributed to 50 respondents.The results showed that the circulation space in the UNILA student dormitory was felt comfortable by the residents. This is shown by the results of the questionnaire about the suitability, suitability of space, activity, visuals, aroma, area, noise, temperature, lighting and security of the dorm which is in accordance with the resident needs.Some of the residents still feel lacking, namely: the bedroom lacks circulation space and the bathroom is less decent, less clean and smelly.